ANALISIS KESULITAN BELAJAR MAHASISWA PADA MATERI HAL SEJAJAR, BERSILANGAN, DAN TEGAK LURUS DALAM MATA KULIAH GEOMETRI RUANG DITINJAU DARI GAYA BELAJAR MAHASISWA - Bambang Eko Susilo (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
The purpose of this research was to describe the profile of student in their type of difficulty experienced, the causes, and the alternative lecturing at Parallel, Skew, and Perpendiculars Materials of Spatial Geometry Lecture in The Perspective of Student’s Learning Styles. The approach in this research is descriptive qualitative. The research subjects numbered 6 students consisting of 2 students with visual style (V), 2 students with auditory style (A), and 2 students with kinesthetic style (K). The research data is in the form of written data and oral data obtained from test, questionnaire, and interview methods. The results showed that: (1) type of difficulties experienced by students of all learning style qualifications are difficult to solve the proving problem, (2) students with visual style (V) has difficulty in accepting material with low proportion of visualizaton, (3) students with auditory style (A) has difficulty in accepting material with low proportion of discussion or explanation in the words and in mathematics writing, (4) while students with kinesthetic style (K) has difficulty in making and understanding images (stereometics), (4) the causes of the difficulties are physiological factors, intellectual factors (learning styles), and paedagogic factors. The alternative lecture which considered an effective lecture with varied method and media-visualization program such as Cabri 3D, Geometer's Sketchpad, and others.